Pengaruh motivasi kerja dan disiplin kerja terhadap kinerja pegawai Yonif 142/KJ - Candra Candra; Zulfina Adriani; Sry Rosita (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to: 1) To determine and analyze the description of work motivation, work discipline and performance of administrative employees of Yonif 142 / KJ, 2) To determine and analyze the effect of work motivation on the performance of administrative employees of Yonif 142 / KJ, 3) To determine and analyze the effect of work discipline on the performance of the administrative staff of Yonif 142 / KJ, and 4) To know and analyze the motivation and work discipline simultaneously affect the performance of the administrative staff of Yonif 142 / KJ by using multiple linear regression analysis tools. Based on the research results indicate that the work motivation in the results of this study is